Effect of Bacterial Vaginosis (BV)-HIV-1 Co-existence on Maternal and Infant Health: A Secondary Data Analysis - Mwenda, Ngugi; Nduati, Ruth; Kosgey, Mathew; Kerich, Gregory (Frontiers in Pediatrics, 2021)
Background: A lactobacillus-rich microbiome forms a defense system against infections. Babies are born sterile and acquire their microbiome from exposure to mothers’ vaginal and rectal microbiota. Bacterial vaginosis (BV), which is characterized by a deficit of the Lactobacilli genera, may predispose women and their babies to an increased frequency of illness. Objective – To determine the effect of BV on HIV-infected women’s post-delivery health as well as the morbidity and mortality of the exposed infant at birth, 6 months, and 12 months of life. Study design -A retrospective cohort study conducted used previously collected data to investigate whether there was an association between BV-HIV-1 infected mothers and subsequent infant morbidity and mortality over a 12-month period Methods:Women were categorized into two groups according to whether they had a positive or negative laboratory-based diagnosis of BV using the Nugent method. The two groups were compared for socio-demographic characteristics, prior pregnancy experience, current pregnancy outcome, and post-delivery morbidity, and duration of hospital stay. BV-exposed and unexposed infants were compared in terms of morbidity and mortality at birth, and in the periods between birth and 6 months and 6-12 months, respectively, based on prospectively collected data of mother’s past and present illness and clinical examination at scheduled and unscheduled visits during the follow-up period of the original study. A generalized estimating equation (GEE) was used to analyze the longitudinally collected data. We used the Kaplan-Meier (KM) method to generate the cumulative hazard curve and compare mortality in the first year of life between the two groups. Results: In total, 365 patients were included in the study. Exposure to BV was associated with the adverse maternal condition and maternal hospital admission but was not linked to any neonatal morbidity at birth. There was a higher frequency of gastrointestinal morbidity among BV-exposed infants. At 6 months, infants of BV-exposed mothers had higher odds of bloody stool dehydration, vomiting, and mouth ulcers. At 12 months, exposure to BV was associated with dehydration and vomiting. KM survival analysis showed non-significant higher trends of deaths among BV-exposed infants (P=0.65).